Interactions between Innate Lymphoid Cells and Cells of the Innate and Adaptive Immune System - Symowski, Cornelia; Voehringer, David (Frontiers in Immunology, 2017)
Type 2 innate lymphoid cells (ILC2s) are a major source of cytokines which are also produced by Th2 cells and several cell types of the innate immune system. Work over the past few years indicates that ILC2s play a central role in regulating type 2 immune responses against allergens and helminths. ILC2s can interact with a variety of cells types of the innate and adaptive immune system by cell-cell contacts or by communication via soluble factors. In this review we provide an overview about recent advances in our understanding how ILC2s orchestrate type 2 immune responses with focus on direct interactions between ILC2s and other cells of the immune system.